Commitment of Political Communication in the Mayor of Banda Aceh - Nasution, Hasyimsyah; Yusnadi, Yusnadi; Zahari, Zahari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Development planning in the city of Banda Aceh is still experiencing various problems and shortcomings both in terms of the substantial process of implementation and supervision. This is because there is still a lack of regional planning apparatus both in terms of quantity and quality and not yet optimal public consultation in taking government policy in development that directly impacts the community, then development plan deliberations and official head work unit forums as a mechanism for community involvement in planning development is not yet up to and maximal. Commitment to the political communication of the mayor of Banda Aceh wants to build the community of the city of Banda Aceh as a model of the civil city. This political commitment arose from the results of the geopolitical analysis, the natural conditions of the region, the Aceh provincial regional development policy and the national development vision, and the strong desire of the mayor himself. The Mayor of Paradigama in building the city of Banda Aceh referred to the concept of building the Prophet in Medina.